SAT0373 Safety of Allopurinol Compared with Other Urate-Lowering Drugs in Patients with Gout: A Systematic Literature Review and Meta-Analysis. (23rd January 2014) - Castrejon, I.; Toledano, E.; Rosario, M. P.; Loza, E.; Perez-Ruiz, F.; Carmona, L.
Abstract : Background: Allopurinol is the most widely used urate-lowering drug (ULD). Drug safety helps, with efficacy and cost, making treatment decisions. Objectives: To analyze the safety of allopurinol in comparison to other ULD Methods: The literature search was performed in MEDLINE, EMBASE, and the Cochrane Library. Selection criteria: a) Patients>18, b) Gout by the ACR criteria or evidence of urate crystal in synovial fluid, c) Comparator (placebo or other ULD), and d) RCTs, cohorts, or meta-analysis. Primary outcomes were: rate of adverse events and death. Quality was assessed with the Jadad's scale. A meta-analysis with fixed effects was performed. Results: From 544 studies, 7 met the eligibility criteria and were included. All RCT with low power for safety. Participants were similar among studies (all RCTs included a mixed population-gout and hyperuricemia). Allopurinol (max. dose 300mg), was compared to febuxostat (40-240mg) in 5 RCTs, benzbromarone and probenecid in 2 RCTs, and to placebo in one. In the RCTs comparing allopurinol with benzbromarone and probenecid, the highest discontinuation rate was with probenecid (26%), followed by allopurinol (11%), and benzbromarone (4%). The incidence of adverse events was similar between allopurinol (range 38.6 to 85) and febuxostat (range 41.8 to 80). Six patients on febuxostat and 3 on allopurinol died during the studies; no deaths were judged related to drug. The combined risk of adverse events was RR = 1.04 (95% CI: 0.98, 1.11) (Fig. 1 ). Image/graph: Conclusions: Allopurinol is a reasonable safe option, similar or slightly better than other ULDs; although the doses studied may be considered low for some patients. Disclosure of Interest: I. Castrejon: None Declared, E. Toledano: None Declared, M. P. Rosario: None Declared, E. Loza: None Declared, F. Perez-Ruiz Consultant for: Menarini, Ardea Biosciences, Novartis Pharmaceutical Corporation, Savient, L. Carmona: None Declared